THE INTERACTION OF DNA WITH CLUSTER RHENIUM COMPOUNDS OF DIFFERENT STRUCTURAL TYPES - Paramonova, K.; Golichenko, A.; Babiy, S.; Shtemenko, A.; Shtemenko, N. (World of Medicine and Biology, 2016)
The interaction of DNA with the cluster compounds of rhenium (III) three structural types differ in the number and orientation of organic ligands around the cluster fragment Re26+ has been studied by electron spectroscopy. The mechanism of interaction of cis-, trans- dicarboxylates and tetracarboxylates of derhenium (III) with a supercoiled polynucleotide by covalent bonding, the formation of the complex compound of rhenium (III) - nucleobase with subsequent unwinding of the helix DNA was confirmed. It is shown that this interaction is different at low and high concentrations of cluster compounds of rhenium and for different structural types of complexes. Redox activation of the interaction between DNA and rhenium compounds, which may explain the previously shown a synergistic or additive anticarcinogenic effect of rhenium and platinum compounds, has been shown.
Keywords: cluster compounds of rhenium(III); DNA; unwinding DNA; redox activation